Usefulness of Yogic Life Style in Enrichment of Education: A Study (ShodhVarta, 2023)
The Indian education system is one of the oldest systems in the world. If we study it seriously, we can find the path towards progressive development in the field of education. "Sa Vidya Ya Vimuktaye", which means that knowledge through which all our attachments, aversions, and dualities come to an end, is the ultimate education. Its three goals are; 1. Self-reliance, 2. Personality development, and 3. Development of social harmony. Education makes a person a responsible citizen, and the person begins to be regarded as proficient and knowledgeable in practical knowledge. The purpose of education has been described as meaningful and holistic by our sages, saints, and ascetics of the age, who say that the process of personality development is accomplished only through the integration of yogic knowledge. In the eyes of the sages, education is that which fulfills the need for completeness in an individual, and yogic knowledge is that which incorporates refinement in a person. Together, they create a comprehensive development of personality. This present theoretical research paper has attempted to explain through the medium of a yogic lifestyle. It strives to help yoga practitioners, seekers of knowledge, and the general public understand the interpretation of a yogic lifestyle in the enrichment of education.